Comparative Anatomical Study of Kidney in adult Male Squirrel (Sciurus anomalus) and Mice (Mus musculus) - Mohammed H. Abed; Shakir M. Mirhish (Indian Journal of Forensic Medicine & Toxicology, 2022)
The current study aimed to investigate the anatomical, morphological, morphometrical data of the kidney in two types of rodent, the squirrel and mice. A total number of 80 kidneys were obtaining from two species which include 40 specimens from squirrels and same number of specimens from mice.Current study showed that the kidneys in two species lay in the abdominal cavity lying retroperitoneal against upper dorsal wall rear of abdominal cavity on either side of vertebral column.The left kidney in squirrel was longer and thicker than right kidney while in mice was reversible and in both animal the left kidney more distant from the median plane than the right but the left kidney in squirrel was larger than right kidney the value.Shape of kidneys in squirrel appeared semi bean like structure but in mice the shape was typical bean like structure, and in both animals the kidneys have smooth surface. Both kidneys of squirrel were by relatively solid texture in contrast with mice kidney.The biometrical measurements of the kidney revealed that the mean weight in squirrel was significantly larger than that of mice. Whereas all micro measurements recorded showed a significant differences between squirrel and mice where the means in squirrel appeared higher than those of mice.Renal artery which arises from abdominal aorta divided to the right branches, the right artery appeared shorter than the left artery, because the left kidney being more distant from the median plane than the right one. The renal artery in mice divided into 3 branches called anterior renal artery, intermediate renal artery and posterior renal artery but in squirrel divided to 2 branches anterior and posterior renal artery. in both animals the 2nd order of artery branches intermediate renal artery divided in mice in 4 inerlober branches but in squirrel the interlober divided into 6 branches